Practical application of sea urchin shell flour supplementation as a stimulant moulting in vannamei shrimp - Heriansah Heriansah; Nursyahran Nursyahran; Nursidi Nursidi; Nur Fajriani Nursida; Najamuddin Najamuddin (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2021)
The practical application of waste recycling as feed supplement is potentially required by small-scale aquaculturist. Furthermore, some of the flour derived from waste sea urchin shells and in adopted in feed, including Deadema setosum were evaluated to estimate the effect on white shrimp Litopenaeus vannamei moulting. This research required the experimentation of four doses with triplicate supplementation (0, 2, 4, and 6 g 100 g-1 of feed) on shrimps four times daily (12% of body weight) for 35 days test period. The juvenile specimens, characterized by an initial weight of 1.610.11 g, were stocked at a density of 12 individuals in a 12 L aquarium. In addition, four compartments were created in each aquarium to facilitate progress observations. The proximate analysis results showed a 53.760.27% calcium content in the shell flour, which significantly increased (P0.05) after higher dose supplementation, in the sequential order 18.650.13%, 20.040.08%, 23.180.10%, and 25.040.11%. Moreover, the frequency and moulting interval with 4 g doses (16.59%0.36% day-1 and 5.910.18 days-1) were significant (P0.05) and considered the best, compared to 0 g (10.48% 0.24% day-1 and 9.970.37 days-1), 2 g (13.49%0.96% day-1 and 8.100.29 days-1), and 6 g (13.81%0.24% day-1 and 7.900.06 days-1). In addition, the respective trend pattern for both parameters increased and decreased at 4 g and 6 g, correspondingly. The highest moulting intensity was also obtained with the 4 g doses, at a range of 4 to 6 times, while the lowest (0 g) varied from 3 to 4 times. These sea urchin shell flour was determined to have numerous practical applications as a feed supplement with proven ability to stimulate moulting in vannamei shrimp.Keywords:MoultingCalciumShellSea urchinFeed supplementationVannamei shrimp